2016
DOI: 10.1186/s12864-016-2981-y
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic, syntenic, and tissue expression analysis of slc22 genes in zebrafish (Danio rerio)

Abstract: BackgroundSLC22 protein family is a member of the SLC (Solute carriers) superfamily of polyspecific membrane transporters responsible for uptake of a wide range of organic anions and cations, including numerous endo- and xenobiotics. Due to the lack of knowledge on zebrafish Slc22 family, we performed initial characterization of these transporters using a detailed phylogenetic and conserved synteny analysis followed by the tissue specific expression profiling of slc22 transcripts.ResultsWe identified 20 zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…OCTN1 belongs to a small sub-family of organic cation transporters that includes only three members, OCTN1, 2 and 3 [1,2]. However, the gene coding for OCTN3 was lost in humans [3,4], that possess only OCTN1 and OCTN2 [5]. Differently from OCTN2, which is a well-acknowledged carnitine transporter, human OCTN1 presents still uncertainties concerning the substrate specificity and, hence, the physiological role.…”
Section: Introductionmentioning
confidence: 99%
“…OCTN1 belongs to a small sub-family of organic cation transporters that includes only three members, OCTN1, 2 and 3 [1,2]. However, the gene coding for OCTN3 was lost in humans [3,4], that possess only OCTN1 and OCTN2 [5]. Differently from OCTN2, which is a well-acknowledged carnitine transporter, human OCTN1 presents still uncertainties concerning the substrate specificity and, hence, the physiological role.…”
Section: Introductionmentioning
confidence: 99%
“…We recently characterized the first uptake transporter of organic anions in zebrafish, named Oatp1d1, and demonstrated its interaction with various environmentally relevant compounds (Popovic et al, 2014). Continuing along this line of research, an uptake transporter of organic cations, Oct1, was also identified in zebrafish, and our first data indicated that Oct1 may function as an integral part of cellular defense against potentially hazardous organic endo-and xenobiotic cationic compounds through biliary and renal excretion (Mihaljevic et al, 2016).…”
Section: Introductionmentioning
confidence: 79%
“…Phylogenetic and conserved synteny analysis revealed orthologous relationships between zebrafish genes -oct1 on chromosome 20 and oct2 on chromosome 17 -and the human OCT gene cluster on chromosome 6. Zebrafish Oct1 is highly expressed in the kidneys of both sexes as well as the male liver (Mihaljevic et al, 2016). The expression profile of Oct1 is similar to its human orthologs, OCT1 and OCT2, which are expressed in the basolateral membranes of the liver and kidney.…”
Section: Introductionmentioning
confidence: 85%
“…OCTs/Octs are highly conserved genes within vertebrate phyla, whose ancestry extends all the way to lamprey and sharks (Zhu et al, 2015). They are represented with three co-orthologs in reptiles, birds and humans, while in teleost fish and amphibians Octs have two and one ortholog(s), respectively (Mihaljevic et al, 2016). Mammalian OCT1-3/Oct1-3 are expressed in a number of toxicologically important tissues essential for metabolization and/or excretion of endo-and xenobiotics, especially liver and kidneys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation